Assessment of a computerised decision support system for allergic rhino-conjunctivitis counselling in German pharmacy - Bertsche, Thilo; Fiederling, Jonas; Schmitt, Simon Petrik Walter; Kaltschmidt, Jens; Seidling, Hanna; Haefeli, Walter E. (International journal of clinical pharmacy, 2012)
Objective In a prospective two-phase intervention study we evaluated a newly developed computerised pharmacy decision support system (PDSS) for the counselling of patients with allergic rhinitis and conjunctivitis. Method Community pharmacists were invited to counsel a virtual patient in a first interview. Immediately thereafter, we trained pharmacists to operate the PDSS, which they applied in a second patient interview immediately following the training. We assessed the completeness of mandatory questions asked as defined by national guidelines. Results Participating pharmacists (n = 50, 78% female, mean age 34 [IQR: 27-40] years, 8 [2-14.5] years of practical experience, 32% specialised in community pharmacy) asked considerably more mandatory questions to confirm appropriateness of self-medication with 7 (5.25-9; 78%) from 9 questions compared to 2 (1-3; 22%) without PDSS (median; P < 0.001). In particular, using the PDSS more than doubled mandatory questions (9/12, 6.25-10; 75% vs. 4/12, 3-5; 33%; P < 0.001) relevant for appropriate drug selection. Conclusion Pharmacists omitted many questions mandatory to assess whether self-medication is appropriate. Using the newly developed PDSS more than doubled the number of mandatory questions asked. The results suggest that the PDSS is ready for evaluation of its impact in real patients.